Magnetic resonance imaging features of gemistocytic astrocytoma. Issue 6 (21st October 2016) - Simkin, Paul M; Yang, Natalie; Tsui, Alpha; Kalnins, Renate M; Fitt, Greg; Gaillard, Frank
Abstract: Introduction: Gemistocytic astrocytoma is the second most common subtype of World Health Organization grade 2 astrocytoma, but has a worse prognosis than other grade 2 lesions. We aim to describe the MR imaging features of histopathologically proven gemistocytic tumours. Methods: Ethics approval was obtained from both institutions. Patient consent was not required for this retrospective study. We reviewed MR imaging findings of 16 consecutive cases of histopathologically proven gemistocytic astrocytoma and anaplastic astrocytoma with gemistocytic features. Results: Average patient age was 48 years, with a 3:1 male to female ratio. Based on our series, the typical appearance of a gemistocytic astrocytoma is a large, heterogeneous mass most commonly supratentorial and lobar. Regions of cyst formation, partial signal suppression on FLAIR images and contrast enhancement are all common features. Additionally, contrary to previous literature that describes gemistocytic astrocytoma as a purely supratentorial lesion, we present two cases of gemistocytic astrocytoma involving the brainstem. Conclusions: The possibility of gemistocytic astrocytoma should be considered in patients presenting with large heterogeneous tumours that have regions of cyst formation, partial FLAIR suppression and contrast enhancement. This may be especially useful in reconciling a lesion with high‐grade MR imaging features with low‐grade histopathology. An infratentorial location does not preclude the diagnosis of gemistocytic astrocytoma.